Knowledge, attitude and practice of breast self- examination among nurses in tertiary hospitals in Malaysia - Raja Gopal, Raja Lexshimi; Md Isa, Zaleha; Daud, Wahida; Mohd Said, Nurumal; Syed Zakaria, Syed Zulkifli (Malaysian Public Health Physicians’ Association, 2014)
Breast self-examination (BSE) is recommended globally as one of the methods in early detection of breast cancer. Little is known about nurses screening behavior related to BSE. A cross-sectional study was conducted to examine the knowledge, attitude and practice of Breast Self Examination (BSE) among nurses. A self-administered questionnaire was sent to a total of 114 nurses working in Obstetrics & Gynaecology wards and clinics of two tertiary hospitals. Among the 114 participants, 111(97.4%) practiced BSE. The mean age of the participants was 34.97(±9.104) years. The mean score of knowledge was 11.07(±1.020) and 81.1% had high knowledge of BSE. Majority (98.2%) of respondents showed good attitude towards BSE. Barriers was found to be a significant predictor and self confidence proved to be an influencing factor on BSE performance. Despite practicing BSE, the number of nurses that examined their breast monthly was only 35.1%. Age, working experience and marital status showed no significant relationship with knowledge and practice of BSE. However, BSE taught during their undergraduate programme was found to have a significant relationship with practice of BSE. Majority of nurses in this study were not complying with MOH recommendation for BSE in terms of frequency. Thus, intervention strategies should focus on educating nurses on performing BSE monthly, in accordance with the Ministry of Health guidelines. This is important as nurses play a primary role in promoting health behaviors in BSE practice and breast cancer awareness among women in this country.